2019
DOI: 10.29333/ejgm/93473
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and compassion fatigue in nurses of neonatal intensive care unit

Abstract: Background: Nurses working in neonatal intensive care units are increasingly faced with a moral distress due to nature of their profession. It is anticipated that this amount of moral distress can have a negative effect on their affection and compassion towards the patient. The aim of this study was to determine the correlation between moral distress and compassion fatigue in NICU Nurses. Method: This descriptive correlational study was conducted with 172 nurses working in the neonatal intensive care unit in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In their study, which is the only one on the subject in the literature, Kılıç et al [1], found that there was no relationship between compassion level and ethical sensitivity. In other studies, it was reported that there was a positive relationship between compassion fatigue and moral distress, and that nurses experiencing compassion fatigue feel moral distress intensely [38,39]. The finding of the study may have resulted from the approaches applied in the institution where the study was conducted, focused on improving the quality of patient care and increasing nurse satisfaction.…”
Section: Discussionmentioning
confidence: 87%
“…In their study, which is the only one on the subject in the literature, Kılıç et al [1], found that there was no relationship between compassion level and ethical sensitivity. In other studies, it was reported that there was a positive relationship between compassion fatigue and moral distress, and that nurses experiencing compassion fatigue feel moral distress intensely [38,39]. The finding of the study may have resulted from the approaches applied in the institution where the study was conducted, focused on improving the quality of patient care and increasing nurse satisfaction.…”
Section: Discussionmentioning
confidence: 87%
“…Saleh et al also showed that higher work experience in neonatal wards is one of the factors associated with higher compassion fatigue. 28 Long-term working in critical care units due to the high sensitivity of nursing care compared to other wards, frequent deaths, multiple cardiopulmonary resuscitation operations, and constant monitoring of patients can be possible causes of fatigue in nurses in these wards.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of the scientific literature demonstrates a central theme describing moral distress as a ubiquitous problem contributing to physical, psychosocial, and emotional effects on nurses resulting in unintended consequences impacting patient care, communication between the interdisciplinary team, the practice environment, and intent to leave the profession. 2,4,5,12,16 The body of research describing the phenomenon of moral distress in NICU nurses focuses on measuring the experience of moral distress, sources of moral distress, the consequences of moral distress, and potential interventions to diminish the negative effects of moral distress. 1,3,[15][16][17][18][19][20] Common ethical challenges in the NICU contributing to moral distress are described in the literature as related to advances in technology, inadequate staffing and resources, caring for infants born at the edge of viability, interdisciplinary communication and hierarchical organizational struggles, and organizational regulations and restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…he phenomenon of moral distress experienced by nurses is recognized as a significant problem with vast implications for nursing practice. [1][2][3][4][5][6][7][8][9] Moral distress in nurses contributes to dissatisfaction with the nursing professional practice role, potentially exacerbating the nursing shortage through attrition. In 1984, philosopher Andrew Jameton 10 first defined the concept of moral distress in nurses as knowing what is right for the patient yet feeling powerless to do the right thing due to unalterable constraints.…”
mentioning
confidence: 99%
See 1 more Smart Citation